Peripheral artery questionnaire improves ankle brachial index screening in symptomatic patients with peripheral artery disease. Issue 12 (31st October 2014) - Kim, B.‐H.; Cho, K.‐I.; Spertus, J.; Park, Y.‐H.; Je, H.‐G.; Shin, M.‐S.; Lee, J.‐H.; Jang, J.‐S.
Summary: Aim: The peripheral artery questionnaire (PAQ) is a disease‐specific health status measure of patients with peripheral artery disease (PAD). Whether the PAQ scores are associated with a PAD diagnosis among patients with symptoms suspicious for PAD is unknown and could help increase the pretest probability of ankle brachial index (ABI) screening among patients with suspicious symptoms. Methods: The PAQ was completed by 567 patients evaluated for potential intermittent claudication at six tertiary centres. Demographics, medical history, physical examination findings and the PAQ domain scores were compared with ABI. A diagnostic threshold < 0.90 for a PAD diagnosis was assessed with a ROC of PAQ scores. The correlation between the PAQ Summary Score and ABI was also calculated. Results: The PAQ Summary Score was significantly lower in patients with low ABI as compared with those having a normal ABI (37.6 ± 19.0 vs. 70.1 ± 22.7, p   < 0.001). The PAQ Summary Score and ABI were highly correlated (r = 0.56, p   < 0.001) and the optimal PAQ Summary Score for predicting low ABI was 50.3 (AUC = 0.86, sensitivity 80.3%, specificity 78.3%). Conclusions: The PAQ Summary Score was associated with an increased likelihood of PAD in patients with suspected PAD symptoms, and a low summary score (≤ 50.3) was an optimal threshold for predicting PAD among patients referred for ABI.